Envenomation by Micrurus annellatus bolivianus (Peters, 1871) coral snake in the western Brazilian Amazon. (August 2019) - da Silva, Ageane Mota; da Fonseca, Wirven Lima; de Araujo Valente Neto, Edgar; Bisneto, Pedro Ferreira; Contreras-Bernal, Jorge; Sachett, Jacqueline; Monteiro, Wuelton Marcelo; Bernarde, Paulo Sergio
Abstract: Bites by Micrurus snakes in Brazilian Amazon represent about 0.4% of snakebite registered in that area. There is not information available about the M. annellatus snakebites In this report, we describe a case of envenoming caused by Micrurus annellatus bolivianus recorded in the municipality of Cruzeiro do Sul, state of Acre, western Brazilian Amazon. On admission, the patient was suffering from mild pain, mild edema and paraesthesia restricted to the site of the bite, darkened vision and nausea. Laboratorial evaluation revealed unclottable blood which improved only after 3 days of follow-up. Envenoming was classified as moderate, and 50 ml of antielapid serum was administered. The next day after the incident, vital signs were normal and the patient had mild thrombocytopenia (133, 000/mm3). The patient did not present any bleeding during the hospitalization. On the fourth day after admission, the patient was discharged alleging no complaints. The patient showed coagulopathy, a rare condition in cases of Micrurus bites. Some areas where there is a lack of knowledge on coral snakebites are listed in this manuscript. Highlights: Bites caused by coral snakes are rarely reported in the Brazilian Amazon. We describe a case of envenoming caused by Micrurus annellatus bolivianus. The patient had unclottable blood and slight thrombocytopenia which are rare conditions in Micrurus bites.